Speech perception and lexical effects in specific language impairment. (2013) - Schwartz, Richard G.; Scheffler, Frances L. V.; Lopez, Karece
Abstract : Using an identification task, we examined lexical effects on the perception of vowel duration as a cue to final consonant voicing in 12 children with specific language impairment (SLI) and 13 age-matched (6;6–9;6) peers with typical language development (TLD). Naturally recorded CV/t/sets [word–word (WW), nonword–nonword (NN), word–nonword (WN) and nonword–word (NW)] were edited to create four 12-step continua. Both groups used duration as an identification cue but it was a weaker cue for children with SLI. For NN, WN and NW continua, children with SLI demonstrated certainty at shorter vowel durations than their TLD peers. Except for the WN continuum, children with SLI demonstrated category boundaries at shorter vowel durations. Both groups exhibited lexical effects, but they were stronger in the SLI group. Performance on the WW continuum indicated adequate perception of fine-grained duration differences. Strong lexical effects indicated reliance on familiar words in speech perception.